Fetal in vivo continuous cardiovascular function during chronic hypoxia. (1st March 2016) - Allison, B. J.; Brain, K. L.; Niu, Y.; Kane, A. D.; Herrera, E. A.; Thakor, A. S.; Botting, K. J.; Cross, C. M.; Itani, N.; Skeffington, K. L.; Beck, C.; Giussani, D. A.
Abstract : Key points: The in vivo fetal cardiovascular defence to chronic hypoxia has remained by and large an enigma because no technology has been available to induce significant and prolonged fetal hypoxia whilst recording longitudinal changes in fetal regional blood flow as the hypoxic pregnancy is developing. We introduce a new technique able to maintain chronically instrumented maternal and fetal sheep preparations under isobaric chronic hypoxia for most of gestation, beyond levels that can be achieved by high altitude and of relevance in magnitude to the human intrauterine growth‐restricted fetus. This technology permits wireless recording in free‐moving animals of longitudinal maternal and fetal cardiovascular function, including beat‐to‐beat alterations in pressure and blood flow signals in regional circulations. The relevance and utility of the technique is presented by testing the hypotheses that the fetal circulatory brain sparing response persists during chronic fetal hypoxia and that an increase in reactive oxygen species in the fetal circulation is an involved mechanism. Abstract: Although the fetal cardiovascular defence to acute hypoxia and the physiology underlying it have been established for decades, how the fetal cardiovascular system responds to chronic hypoxia has been comparatively understudied. We designed and created isobaric hypoxic chambers able to maintain pregnant sheep for prolonged periods of gestation under controlled significant (10% O2 ) hypoxia, yielding fetal mean P a O 2 levels (11.5 ± 0.6 mmHg) similar to those measured in human fetuses of hypoxic pregnancy. We also created a wireless data acquisition system able to record fetal blood flow signals in addition to fetal blood pressure and heart rate from free moving ewes as the hypoxic pregnancy is developing. We determined in vivo longitudinal changes in fetal cardiovascular function including parallel measurement of fetal carotid and femoral blood flow and oxygen and glucose delivery during the last third of gestation. The ratio of oxygen (from 2.7 ± 0.2 to 3.8 ± 0.8; P  < 0.05) and of glucose (from 2.3 ± 0.1 to 3.3 ± 0.6; P  < 0.05) delivery to the fetal carotid, relative to the fetal femoral circulation, increased during and shortly after the period of chronic hypoxia. In contrast, oxygen and glucose delivery remained unchanged from baseline in normoxic fetuses. Fetal plasma urate concentration increased significantly during chronic hypoxia but not during normoxia (Δ: 4.8 ± 1.6  vs . 0.5 ± 1.4 μmol l −1, P<0.05). The data support the hypotheses tested and show persisting redistribution of substrate delivery away from peripheral and towards essential circulations in the chronically hypoxic fetus, associated with increases in xanthine oxidase‐derived reactive oxygen species. Key points: The in vivo fetal cardiovascular defence to chronic hypoxia has remained by and large an enigma because no technology has been available to induce significant and prolonged fetal hypoxia whilst recording longitudinal changes in fetal regional blood flow as the hypoxic pregnancy is developing. We introduce a new technique able to maintain chronically instrumented maternal and fetal sheep preparations under isobaric chronic hypoxia for most of gestation, beyond levels that can be achieved by high altitude and of relevance in magnitude to the human intrauterine growth‐restricted fetus. This technology permits wireless recording in free‐moving animals of longitudinal maternal and fetal cardiovascular function, including beat‐to‐beat alterations in pressure and blood flow signals in regional circulations. The relevance and utility of the technique is presented by testing the hypotheses that the fetal circulatory brain sparing response persists during chronic fetal hypoxia and that an increase in reactive oxygen species in the fetal circulation is an involved mechanism.